Gaze-holding nystagmus in chronic progressive external ophthalmoplegia: a case report - Jung, Eugene; Choi, Seo-Young; Choi, Jae Hwan; Choi, Kwang-Dong (Research in vestibular science, 2025)
We report a patient with chronic progressive external ophthalmoplegia (CPEO) who developed bilateral horizontal gaze-holding nystagmus, a previously unreported phenomenon. Video-oculography showed marked slowing of horizontal and vertical saccades, and bilateral horizontal gaze-evoked nystagmus with decreasing-velocity slow-phases waveforms. Horizontal rebound nystagmus was also observed. No abnormalities were identified in the brainstem or cerebellum on brain magnetic resonance imaging. A genetic analysis demonstrated a heterozygous missense mutation c.311A>G (p. D104G, rs28999114) in the SLC25A4 gene. Twitch motoneurons of the global layer receive inputs from premotor areas involved in the generation of eye movement, such as saccadic burst neurons, while non-twitch motoneurons of the orbital layer receive inputs from the medullary structures concerned with gaze-holding. In our patient with CPEO, the presence of omnidirectional ophthalmoplegia and bilateral horizontal gaze-holding nystagmus may indicate the involvement of the global layers of all extraocular muscles, as well as the orbital layers of the horizontal extraocular muscles.